A STUDY OF COAST PROTECTION CONSTRUCTIONS BUILT WITH THE USE OF RECYCLED CONSTRUCTION MATERIALS AND THEIR NEGATIVE IMPACT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Different types of materials are used in hydraulic structures and coast protection constructions. These materials can be of natural (e.g. stone) and artificial origin (concrete, metal). The main trends typical for building construction now are as follows: cutting a share of natural materials and reusing waste products of dismantling construction objects. As a result of recycling it is possible to produce building materials that look like and have properties characteristic of natural stone materials, gravel, in particular. While gravel is being processed, it is possible to predict that it would obtain such characteristics as grade, frost resistance and strength. Reuse of recycled construction materials is a challenge, because this type of waste can hardly be reduced in volume and requires considerable space for burial. We propose to use gravel produced by processing in hydraulic engineering objects, i.e. in coast protection constructions. For that, we analyzed waste materials characteristics to justify their use in hydraulic structures. The research proved that strength of gravel produced by processing was sufficient enough. On the other hand, its frost resistance and fineness did not satisfy the requirements to materials used in coast protective structures. Besides, the construction of such structures causes water pollution as inert materials placed in waterbodies increase water turbidity. As a large part of the structure is located directly in the waterbody, during the period of the construction inert materials are supposed to be dumped. In this period the water body is filled with a significant amount of fine particles, which leads to an increase in turbidity at the construction site. Thus, we come to the conclusion that it is possible to reuse recycled construction materials in hydraulic engineering structures only on condition of their additional after-treatment processing. We offer to mix gravel produced by processing with cement mortal. As a result we obtain no-fines concrete, which is further processed by hot procedure (with bituminous materials). No-fines concrete can be produced in the form of precast units of 1,4×1,4×0,5 m. The use of prefabricated units will allow to avoid waterbody pollution and protect it from fine particles. Further processing by bituminous materials will enhance its frost resistance and reliability, which in turn will prevent contamination of the water body in the period of coast protection constructions usage.